Current understanding of the Streptococcus bovis/equinus complex and its bacteriophages in ruminants: a review - Park, Seon Young; Seo, Seongwon; Kim, Ji Hyung (Frontiers in Veterinary Science, 2025)
Streptococcus bovis/Streptococcus equinus complex (SBSEC) comprises eight (sub)species, with several opportunistic pathogenic members. These SBSEC species are associated with metabolic disorders in ruminants, resulting in economic losses to the global livestock industry. Moreover, the emergence of antimicrobial resistance (AMR) in SBSEC strains, particularly against commonly used antibiotics, poses serious concerns to the livestock industry. Therefore, alternative approaches to control SBSEC infections have garnered increased attention, and several applications of bacteriophages (phages) have exhibited promising results. Research on SBSEC and their phages has been limited, particularly in livestock production. However, advancements in molecular techniques and a growing interest in alternative strategies to combat AMR have brought SBSEC and their phages into the spotlight. Molecular techniques, such as whole-genome sequencing, have revolutionized the accurate identification and classification of SBSEC, resulting in the elucidation of their ecological and pathogenic roles. SBSEC-infecting phages exhibit remarkable diversity and potential as biocontrol agents, with phage-derived endolysins offering targeted regulation of the SBSEC populations in the rumen. Despite recent achievements, knowledge gaps exist in understanding phage–host interactions and evaluating the efficacy of phage in biologically relevant models, warranting the integration of ex vivo, in vivo, and in silico approaches. Here, we comprehensively review the current knowledge regarding the taxonomy, AMR characteristics, and diversity of SBSEC, and the potential of SBSEC-specific phages, focusing on recent advances in basic research and biotechnological applications in ruminants. Harnessing the potential of SBSEC-specific phages and their derivatives as innovative solutions should help promote overall animal health and the production of antibiotic-free livestock.